Design of Denotative and Directive Text Poster as Cognitive Stimulant in Basic Education Institution - Fauzi Rahman; Azhari Amri (Universitas Indraprasta PGRI, 2018)
In the directive function, the language not only keeps the listener doing something, but also performs the activities that the speaker wants. The directive function is oriented to the message recipient. Based on the directive function of this language, it is hoped that this activity can be effectively applied to students as learners in the school to get positive messages from sentences that will be visualized in the school environment in the form of educative posters. This research is conducted in thise basic education institutions have targeted the achievement of s research is conducted in this basic educational institution has the target of achievement among which is giving education through poster design work which socialize code of ethics to solve common problem in school environment.. By making design work based on the need to raise the school code of ethics, it is hoped that this kind of community service activity will change the way of thinking of the school people to practice the behavior of the code of ethics both in school and community.